Circulating Calreticulin Is Increased in Myelofibrosis: Correlation with Interleukin-6 Plasma Levels, Bone Marrow Fibrosis, and Splenomegaly. (8th September 2016) - Sollazzo, Daria; Forte, Dorian; Polverelli, Nicola; Perricone, Margherita; Romano, Marco; Luatti, Simona; Vianelli, Nicola; Cavo, Michele; Palandri, Francesca; Catani, Lucia
Abstract : Myelofibrosis (MF) is a clonal neoplasia of the hemopoietic stem/progenitor cells associated with genetic mutations in the Janus kinase 2 ( JAK2 ), myeloproliferative leukemia virus oncogene ( MPL ), and calreticulin ( CALR ) genes. MF is also characterized by a state of chronic inflammation. Calreticulin (CRT), as a multifunctional protein, is involved in a spectrum of cellular processes including inflammation, autoimmunity, and cancer initiation/progression. Based on this background, we hypothesised that in MF circulating CRT might reflect the inflammatory process. In the present study we show that circulating CRT is increased in MF patients compared to healthy controls. Also, in MF, CRT levels highly correlate with bone marrow fibrosis, splenomegaly, and Interleukin-6 (IL-6) plasma levels. In turn, higher IL-6 levels also correlated with disease severity in terms of increased spleen size, bone marrow fibrosis, number of circulating CD34 + cells, and lower hemoglobin values. These results demonstrate that the circulating CRT takes part in the inflammatory network of MF and correlates with aggressiveness of the disease.